Decision Support System for Selecting Cryptocurrency Exchange Platforms Using the Multi Attribute Utility Theory (MAUT) Method Based on a Website: Sistem Pendukung Keputusan Pemilihan Platform Cryptocurrency Exchange Menggunakan Metode Multi Attribute Utility Theory (MAUT) Berbasis Website - Arsendy Putra, R. Gading Utama; Utami, Ardhini Warih (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
In the rapidly evolving digital era, the financial industry has undergone significant changes with the emergence of cryptocurrency in Industry 4.0. In Indonesia, the number of cryptocurrency holders has increased rapidly, leading to the proliferation of many cryptocurrency exchange platforms to meet the needs of individual traders, financial institutions, investors, and novice users who lack foundational knowledge about blockchain technology or market dynamics. This complexity in choosing the right platform necessitates an effective decision support system. Previous research has proposed decision-making methods such as the Preference Selection Index (PSI) and the Analytical Hierarchy Process (AHP). To enhance the accuracy of platform selection, this study employs the Multi-Attribute Utility Theory (MAUT) and Forward Chaining methods. MAUT enables the assessment of pre-determined criteria and weights, while Forward Chaining simplifies the decision-making process by providing recommendations based on user preferences. By utilizing MAUT and Forward Chaining, this system assists users in understanding the essential aspects of selecting a platform and provides recommendations that align with their preferences and needs. The criteria for this decision-making process are based on a pre-survey conducted within the SGB x Crypto cryptocurrency community, and the MAUT weights and preferences were determined through interviews with cryptocurrency experts. Based on the results of questionnaires and interviews, five main criteria were selected: security with a weight of 0.35 (K1), feature completeness with a weight of 0.2 (K2), customer service quality with a weight of 0.1 (K3), regulation with a weight of 0.2 (K4), and the number and variety of coin assets with a weight of 0.15 (K5). The five evaluated cryptocurrency exchange platforms are Tokocrypto (A1), Pintu (A2), Indodax (A3), Binance (A4), and Bybit (A5). This study results in the implementation of a web-based decision support system for selecting cryptocurrency exchange platforms using MAUT and Forward Chaining. This system helps novice users understand the crucial aspects of choosing a platform and provides recommendations for cryptocurrency exchange platforms that suit their preferences.